2020
DOI: 10.1016/j.actamat.2019.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformation induces plasticity with negligible damage in ceria-stabilized zirconia-based ceramics

Abstract: Ceramics and their composites are in general brittle materials because they are predominantly made up of ionic and covalent bonds that avoid dislocation motion at room temperature. However, a remarkable ductile behavior has been observed on newly developed 11 mol.% ceria-stabilized zirconia (11Ce-TZP) composite containing fine alumina (8vol.% Al 2 O 3 ) and elongated strontium hexa-aluminate (8vol.% SrAl 12 O 19 ) grains. The assynthesized composite also has shown full resistance to Low Temperature Degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
26
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 81 publications
5
26
0
1
Order By: Relevance
“…Only few judiciously manufactured zirconia composites showed the capability of inelastic deformation in combination with biaxial bending strength (~1 GPa), toughness (~ 10 MPa•m 1/2 ) and high reliability (Weibull modulus > 20) [21,27,29]. These composites include 10Ce-TZP-30Al2O3 nanocomposites with inter-and intragranularly located alumina particles [21] and three-phase ZA8Sr8Ce11 (11Ce-TZP with 8 vol% Al2O3 and 8 vol% SrAl12O19) composites [20,26,27,34]. It has also been shown that the plastic deformation in the ZA8Sr8Ce11 composite was not associated to crack occurence or phase debonding inside the transformation bands, revealing a purely elastic-plastic behavior driven by phase transformation and not by microcracking [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few judiciously manufactured zirconia composites showed the capability of inelastic deformation in combination with biaxial bending strength (~1 GPa), toughness (~ 10 MPa•m 1/2 ) and high reliability (Weibull modulus > 20) [21,27,29]. These composites include 10Ce-TZP-30Al2O3 nanocomposites with inter-and intragranularly located alumina particles [21] and three-phase ZA8Sr8Ce11 (11Ce-TZP with 8 vol% Al2O3 and 8 vol% SrAl12O19) composites [20,26,27,34]. It has also been shown that the plastic deformation in the ZA8Sr8Ce11 composite was not associated to crack occurence or phase debonding inside the transformation bands, revealing a purely elastic-plastic behavior driven by phase transformation and not by microcracking [34].…”
Section: Introductionmentioning
confidence: 99%
“…These composites include 10Ce-TZP-30Al2O3 nanocomposites with inter-and intragranularly located alumina particles [21] and three-phase ZA8Sr8Ce11 (11Ce-TZP with 8 vol% Al2O3 and 8 vol% SrAl12O19) composites [20,26,27,34]. It has also been shown that the plastic deformation in the ZA8Sr8Ce11 composite was not associated to crack occurence or phase debonding inside the transformation bands, revealing a purely elastic-plastic behavior driven by phase transformation and not by microcracking [34]. However, all these observations were conducted after loading and a clear clarification about the t-m transformation process in correlation with crack initiation and propagation is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…However, only very few reported studies were available on lanthanum hexa-aluminate containing zirconia based ceramics [29][30][31][32][33]. Furthermore, different forms of elongated precipitates can be generated by different processing methodologies even with the same overall composition [14,25,34]. In-situ formed large-sized strontium or lanthanum hexa-aluminate elongated precipitates were reported to have a negative effect on both fracture toughness and strength of 12Ce-TZP based composites, as compared to alumina particle additions [25].…”
Section: Introductionmentioning
confidence: 99%
“…In alloys with metallic bonds, plastic deformation is realized by local atomic displacements that proceed through switching one or a few interatomic bonds at a time along the lattice planes, also known as dislocation motion (25,26). Stress-induced phase transformation and the consequent plasticity have been realized in metallic materials and even in ionically bonded ceramics such as ZrO 2 (27)(28)(29)(30)(31)(32) with nondirectional bonding. Although this mechanism has enabled plastic deformation in other materials, it has remained elusive in covalently bonded ceramics (33), mainly because of the directionality of covalent bonds.…”
mentioning
confidence: 99%